Comparison of cerebrospinal fluid Cytochrome-c and Caspase-9 as biomarkers for newborns with hypoxic ischemic encephalopathy with non-asphyxiated babies and followup of these biomarkers after day 7 - Kushwah, Supriya; Kumar, Ashok; Basu, Sriparna; Krishnamurthy, Sairam; Kumar, Ashutosh (International Journal of Research in Medical Sciences, 2017)
Background: There are very less previous study for cytochrome–c and caspase-9, the key players in apoptotic cell death, in human newborns. The objective was to measure the level of cerebrospinal fluid biomarkers cytochrome –c and caspase -9 in newborns with hypoxic ischemic encephalopathy and comparison with clinically suspected sepsis controls and to compare these after 7 days. Methods: We compared 50 hypoxic babies with 20 newborns with clinically suspected sepsis at median age of day-3 and 9 in cases and day-1 in controls. Results: In the present study in sample-1 we observed a significant increase in the levels of cases cytochrome c (1.46 ± 0.71 ng⁄mL) and caspase- 9 (0.29 ± 0.27 ng⁄mL) when compared to controls cytochrome-c (1.02+0.27 ng⁄mL) and caspase -9 (0.13+0.16 ng⁄mL) with significant p-value of 0.001 and 0.009 respectively. In sample -1 Cytochrome-c, P- value was significant when compared stage –III (1.74 ± 0.68) with stage-I (0.82 ± 0.43) and stage –II (0.99 ± 0.18). Similarly in Caspas-9 P-value was significant when compared between stage-III (0.38 ± 0.30) with stage-I (0.11 ± 0.07). In sample -2 P- value was significant when compared stage –III (1.68 ± 0.50) with stage-I (1.01 ± 0.14) and stage –II (0.94 ± 0.38). Similarly in Caspas-9 P-value was significant when compared between stage-III (4.84 ± 2.44) with stage-I (0.13 ± 0.10) and stage –II (0.13 ± 0.11). Conclusions: First time done in human newborns with asphyxia, showing that CSF Cytochrome- c and Caspase 9 increases significantly. In sample-2, the caspase 9 levels showed a further increase, whereas cytochrome c levels decreased from the sample 1 value indicating that neuroprotection time should be increased.